CONSTRAINTS ON STUDIES OF METAMORPHIC K-NA WHITE MICAS - Guidotti C.V.; Sassi F.P. (My University, 2002)
Micas have been studied for many important and highly interesting reasons by a wide range of workers, e.g., engineers, physicists, chemists, and Earth scientists. Our focus includes only aspects related to the Earth sciences, specifically the mineralogy and petrology of natural metamorphic rocks, and particularly the occurrence of micas in such rocks. Mineralogists and petrologists have studied micas extensively in order to understand the controls on their genesis, and hence, that of the rocks containing them. Mineralogists have also studied them with a focus aimed at understanding their very interesting crystallochemical aspects irrespective of their petrologic implications. By far the most common micas are (1) the trioctahedral Fe-Mg micas broadly described as “biotites,” and (2) the dioctahedral “white” micas muscovite, paragonite and margarite. An enormous literature exists on the mineralogical and petrologic aspects of these two groups. For our purposes we will concentrate on the dioctahedral, Na-K “white” micas as found in metamorphic rocks, especially metapelites. Some discussion of the “biotites” will be included when it provides especially good opportunities for addressing the goals of this paper. There can be a complete merging of approaches and aims of the mineralogic and petrologic studies of micas, but not uncommonly they are conducted quite independently and unconcerned with each other. We believe this is unfortunate as will become clear in our presentation below. Despite the merging of some studies over both petrology and mineralogy, for the purposes of our discussion we will define them as end-member approaches as follows. Mineralogic studies are concerned with innate aspects of the minerals themselves, with little or no regard for the petrologic setting from which the mineral has been obtained; e.g., studies of samples from museum collections. Commonly such studies try to gain insights regarding the compositional and crystal structural (a crystallochemical understanding) or physical (e.g., …